Análise de glucuronídeos em urina humana com injeção direta de amostras por cromatografia líquida acoplada à espectrometria de massa - Castral, Thaís Corrêa (2013)
This work describes the results obtained from studies carried out to quantify phenyl-β-D-glucuronide (FG) and nitrophenyl-β-D-glucuronide (NFG) in human urine by direct injection sample using LC-MS/MS system. The columns RAM-BSA SAX and RAM-BSA C8 were prepared and evaluated in relation to their exclusion capability of urine macromolecules and retention capability of FG by direct injection samples. Both columns presented good retention capability for glucuronide, however, the RAM-BSA SAX column was more efficient in exclusion since this column did not have any interferences eluting after the exclusion time. However, the RAM-BSA SAX column can not be used for FG quantification by LC-MS/MS because the chromatographic condition of this column presented high buffer concentration (40 mM ammonium formate), which resulted in total suppression of the FG signal. Therefore, the column RAM-BSA C8 was selected for the development of the methods. In this study we evaluated triple quadrupole (QqQ) and ion trap (IT) mass spectrometry for both selected glucuronides. It was not possible to obtain selectivity in the analytical conditions developed using UHPLC-QqQ. When we used the IT analyzer, we obtained selectivity in a multidimensional mode for the FG using the column RAM-BSA C8 in the first dimension and the column Ascentis Express F5 in the second dimension. For the NFG we achieved selectivity in a unidimensional mode. The figures of merit obtained with external standarization calibration curve with spiked pooled urines were accurate and precise. For FG, the LQ and LD were 1.0 μg/mL and 0.5 μg/mL, respectively, and to NFG, the LQ and LD were 4.0 μg/mL and 3.0 μg/mL. For the method application we adopted calibration by standard addition to minimize the individual differences between urine donors. To all six toxicological samples analyzed, just one exceeded the regulatory limits for urinary phenol. For NFG, there were no toxicological samples available, thus the method was applied in spiked samples in the laboratory.